Kedudukan Menteri Triumvirat dalam Mengisi Kekosongan Jabatan Presiden di Indonesia dalam Perspektif Siyasah Syar’iyyah - Siti Maryam; Hafidhul Umami; Avivul Huda (Bahasa Indonesia, 2025)
This study analyzes the position of the Triumvirate Ministers in filling the vacancy of the President's office in Indonesia from the perspective of Siyasah Syar'iyyah. The Triumvirate Ministers, consisting of the Minister of Foreign Affairs, the Minister of Home Affairs, and the Minister of Defense, play a crucial role as interim presidential executors when simultaneous vacancies of the President and Vice President occur, as stipulated in Article 8 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia. From the perspective of Siyasah Syar'iyyah, this mechanism aligns with the concept of temporary leadership to prevent harm due to power vacuums. Imam Al-Mawardi emphasizes the importance of promptly filling leadership vacancies to maintain stability and the welfare of the ummah. This research employs a normative juridical method with statutory, historical, and comparative approaches. The findings indicate that the position of the Triumvirate Ministers as interim presidential executors has a strong foundation both in Indonesia's positive law and in the concept of Siyasah Syar'iyyah, thereby preventing harm due to power vacuums.